FOLLICLE SYNDROME NOT BROKEN LUTEINIZING - Coyotupa, Juan (2015)
144 patients who follicle syndrome luteinised not broken with 450 menstrual cycles in which ovulation had ultrasounds to, determination of prolactin, progesterone and evaluated diagnostic laparoscopy. It has been found that 72% of patients had an organic cause as adhesions, endometriosis or both. 28% of patients remaining 18% was associated with hyperprolactinemia as a cause of the syndrome.